Public transport decarbonization via urban bus fleet replacement in Portugal - Ribeiro, Paulo (2022)
The transport sector accounts for around one-quarter of the GHG emissions in Europe, and, in Portugal, it represents almost one-third of the total emissions to the atmosphere. Unfortunately, these emissions have increased in recent years. Hence, cities and countries need plans to decarbonize their public transport fleets, and, more specifically, to replace fossil-fueled buses with electric buses that produce zero CO2 emissions. Thus, the main objective of this paper is to present a method to decarbonize the bus fleet in Portugal by a scheduled replacement of the current fleet, which is fueled by fossil fuels, with a completely electric fleet, in fourteen years. The study shows that it is possible to replace all Portuguese urban bus fleets with electric vehicles considering that all vehicles will be replaced when reaching the age of 14 years. Replacing the urban bus fleet with zero-emission buses would aid policymakers and bus companies to reduce the GHGs, and therefore contribute to fulfilling the Sustainable Development Goals of the United Nations 2030 Agenda for Sustainable Development, namely, Goal 13—take urgent action to combat climate change and its impacts.